Organizational leadership - Bratton, John (Core textbook, 2020)
Organizational Leadership provides an accessible, critical and engaging analysis of what constitutes 'leadership' today. Demonstrating leadership as an interconnected process between leaders, followers and context, the book ensures a rounded understanding of theory and practice to support students throughout their course and future career. Part 1: Contextualising Leadership examines the internal and external forces influencing leadership, addressing issues such as ethics, power, culture and innovation. Part 2: Leadership Theories reviews and analyses traditional and contemporary theories of leadership. Part 3: Managing People and Leadership builds on the idea of leadership as a human process and considers how complementary aspects of HRM can inform leadership practice and its outcomes on employees and organizational performance. Part 4: Contemporary Leadership considers topical issues including the shift of leadership studies towards followership, gender and leadership and pro-environmental leadership. Bringing complex theories and concepts to life through a range of case studies and examples, the book is further supported by a series of fascinating expert video conversations with those in leadership roles. From small social businesses to major multi-nationals, from the NHS to the frontline military teams, the videos offer a unique insight into the diverse reality of leadership in practice today.